PEMBENTUKAN KARAKTER SISWA DENGAN SISTEM BOARDING SCHOOL - Muhamad Sholikhun (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The focus in this study was the implications of boarding school system at Asri Islamic Boarding School on the character building of students at SMP Syubbanul Wathon Tegalrejo, especially regarding how to develop and implement boarding school system to the character education of the students at at SMP Syubbanul Wathon Tegalrejo. This was a qualitative research, conducted at SMP Syubbanul Wathon Tegalrejo. The data collection techniques were observation, interview, and documentation. The data validity test was performed using triangulation of data sources. The data analysis used descriptive method. To conclude this research, boarding school model that supports character education of students is in the form of integrated learning through teaching-learning method (dirasah wa ta’li), making habit of virtuous behavior (ta’dib), spiritual activities (riyadhah), as well as giving a role model (uswah hasanah) by kyai/nyai and ustadz. In addition, the students’ activities are also monitored through regulations. All these are to support an education system that could result in virtuous character building of the students, where they are expected to be independent in many aspects of their daily lives.